Evaluación de 2 niveles de harina de tubérculos de rechazo de papa china (Colocasia Esculenta) en reemplazo del maíz en la alimentación de pollos de engorde - Romero Ramírez, Jéssica Alejandra (2023)
The current research work was made in the Ambato city, in the Martínez parish, which it was used 90 broilers with an average initial weight 39.5g. The aim was to integrate flour from rejected Chinese potato (Colocasia esculenta) tubers as raw material in the feed formulations elaboration for broiler chickens and its impact on production costs. For this, it was developed two balanced formulations, being T1 with the addition 5% Chinese potato rejection tuber meal and T2 with the addition 10% Chinese potato rejection tuber meal, which were added to the base diet. (balanced: own formulation), to be compared them in relation to the control treatment or T0, this being the base diet (balanced: own formulation), in order to keep the productive parameters in the birds with an optimal result and the attainment of better economic yields. The treatments assessment lasted 49 days; concluding, what according to the results got for the measured parameters this research, the treatment with highest value was T2, getting an increase weight in the last week 728.40g, likewise, it was reported a food consumption 1246g, thanks to the greater acceptance in palatability and a feed conversion 1.69 in the assessment last week. Since the economic parameter perspective, it can determine, what the formulation with the Chinese potato rejection tuber flour lowest percentage, treatment T1 decreases production costs and gives significant results in relation to the control treatment.